2011
DOI: 10.2165/11592120-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Nail Disorders

Abstract: Fingernails and toenails are important organs of our body, serving as protection for the tips of fingers and toes. Fingernails also enhance fine touching and tactile sensitivity, as well as aid in the picking up of small objects. Healthy-looking nails are an important part of an individual's body image, and any nail abnormalities may be considered by patients as a significant cosmetic problem, markedly influencing their self-esteem. However, recent data have indicated that nail lesions are not only important b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
53
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 50 publications
2
53
0
1
Order By: Relevance
“…Van Laborde et al have shown that there is an 80% to 90% lifetime incidence of nail involvement in psoriatic patients [4]. The presence of nail involvement of psoriasis is associated with an increase in patient-reported pain complaints, functional impairment and social burden, resulting in a significant restriction of daily activities and quality of life as well as resistance to treatment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Van Laborde et al have shown that there is an 80% to 90% lifetime incidence of nail involvement in psoriatic patients [4]. The presence of nail involvement of psoriasis is associated with an increase in patient-reported pain complaints, functional impairment and social burden, resulting in a significant restriction of daily activities and quality of life as well as resistance to treatment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Nail psoriasis is usually diagnosed only by physical examination, observed features depending on nail matrix or nail bed involvement. The presence of nail psoriasis is clinically relevant as patients often complain of pain, functional impairment and social burden, resulting in a significant restriction of daily activities and quality of life [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of onychomycosis has been correlated with environmental risk factors such as occlusive footwear, occupational hazards, trauma, lack of rotation of shoes being worn, exposure in moist environments such as health clubs and swimming pools, family members with onychomycosis and pets as well as surfaces they frequent and potentially contaminate within the household [4,5,6,7]. Onychomycosis is associated with patient dissatisfaction and decreased quality of life [8,9]. It is a common comorbidity of advanced age [10], diabetes [11,12], peripheral vascular disease [13], HIV [14], immunosuppression [15], obesity [16] and smoking [13].…”
Section: Introductionmentioning
confidence: 99%